Effect of Placenta Tissue Storage Term under 4Ð¾Con Chorion Villi Ultrastructure - Repin, N. V.; Tsupikov, O. M.; Govorukha, T. P.; Yurchenko, T. N. (Problems of Cryobiology and Cryomedicine, 2002)
The effect of storage duration of placenta tissue under 4oC on the chorion villi ultrastructure has been studied. It has been noted, that after 2 days of hypothermic storage of placenta tissue the ulstrastructural changes in chorion villi, being of destructive character, occur.